Determinants of the uptake of intermittent preventive treatment of malaria in pregnancy with sulphadoxine pyrimethamine in Sabatia Sub County, Western Kenya - Mutanyi, JA; Onguru, DO; Ogolla, SO; Adipo, LB (Springer, 2021)
Background: Annually, 125.2 million pregnant women worldwide risk contracting malaria, including 30.3 million and 1.5 million in Sub-Saharan Africa and Kenya respectively. At least three doses of sulphadoxine pyrimethamine for intermittent preventive treatment of malaria in pregnancy (IPTp-SP) is recommended for optimal benefit. Kenya recorded low IPTp-SP optimal uptake in 2015. This study investigated the prevalence of and factors influencing IPTp-SP optimal uptake in Sabatia Sub County, Western Kenya.